Electronic structure and magnetic properties of transition metal kagome metal–organic frameworks. Issue 36 (12th September 2022) - Kang, Seungjin; Yu, Jaejun
Abstract : From the first-principles calculations, we provide a microscopic understanding of the crystal structure, magnetic ground states, and anisotropy of a series of transition metal atoms and ligands of the two-dimensional kagome metal–organic frameworks. Abstract : Kagome metal–organic frameworks (MOFs) are considered a new class of materials that can host two-dimensional (2D) magnetism and correlated electron phenomena such as superconductivity and quantum anomalous Hall effect. Despite its potential for spintronics applications and others, the systematic understanding between the electronic structure and magnetic properties of kagome MOFs is still missing. This work determines the crystal structure, magnetic ground states, and anisotropy of a series of transition metal atoms and ligands from first-principles calculations. We reveal that the coexistence of covalent and ionic bonding characters of 3d orbitals is a distinctive feature of the 2D kagome MOFs. Furthermore, we demonstrate that the occupancies of active bands near the Fermi level are responsible for different superexchange mechanisms: the partially filled bands with empty for V and Co MOFs lead to antiferromagnetic ordering, and the partially filled bands with full for Mn, Fe, and Co MOFs lead to ferromagnetic ordering between transition metal ions. It is pointed out that the bands are formed through dpπ-hybridization between the transition metal d yz, d zx and ligand p z orbitals in the square planar coordination of metal atoms. This mechanism provides valuable insights into understanding magnetism in 2D kagome MOFs.